A flow-based mobility architecture in multihomed nemo to minimize registration delay - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abd Latif, Suhaimi; Hasan, Mohammad Kamrul (Asian Research Publishing Network (ARPN), 2015)
With the growing development of Different Access Technology Type (DATT), a serving Mobile Router (MR) is capable to connect with multiple interfaces concurrently during handoff among DATT. Correspondingly, a shared prefixbased based flow movement in multihomed Network Mobility (NEMO) can be achieved in order to transfer real time application flows among the most appropriate Access Technology Type (ATT) dynamically to provide better Quality of Service (QoS) for real time scenarios in NEMO. Although Multiple Care of Address (MCOA) registration between serving MR along with its Home Agent (HA) can overcomes some of the multihoming issues for NEMO, but still required a dynamic flow redirection mechanism leads to signaling overhead issues to support mobility management in NEMO. The aim of this paper is to propose a Shared Prefix-based Flow mobility scheme in multihomed NEMO (SPF-NEMO) which is based on PMIPv6 to reduce registration delay during inter mobility handoff as well. Moreover, numerical framework is formulated to evaluate the outcomes of the SPF-NEMO scheme. Through the performance analysis with results, it is confirmed that SPF-NEMO provides better solution related to extra registration delay during handoff among DATT.